Stress, Coping, and Psychiatric Symptoms in Pregnant Women in Outpatient Care During the 2021 Second-Wave COVID-19 Pandemic - Penengo, Chiara; Colli, Chiara; Cesco, Maddalena; Croccia, Veronica; Degano, Matilde; Ferreghini, Alessandra; Garzitto, Marco; Lobel, Marci; Preis, Heidi; Sala, Alessia; Driul, Lorenza; Balestrieri, Matteo (Frontiers in Psychiatry, 2022)
Aims: Women face many sources of stress throughout their lives, and some periods are particularly sensitive; pregnancy is one of them. The COVID-19 pandemic is a likely source of additional stress for pregnant women. Moreover, there is evidence that pregnant women have experienced high levels of anxiety and depression symptoms during the pandemic. Our study aimed to evaluate the association of pregnancy-specific stress, pandemic-related stress, and coping strategies with anxiety, depressive and obsessive-compulsive symptomatology in Italian women during the second wave of the COVID-19 pandemic (December 2020 – June 2021). We also investigated whether there were differences in these levels of psychopathology compared to a prior study conducted during the first pandemic wave (April – August 2020) in Italian pregnant women. Methods: We assessed 325 pregnant women receiving outpatient prenatal care, using the Revised Prenatal Distress Questionnaire (NuPDQ), Pandemic-Related Pregnancy Stress Scale (PREPS), the Revised Prenatal Coping Inventory (NuPCI), General Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-2 (PHQ-2), and Obsessive-Compulsive Disorder (OCD) screening. The main analysis was conducted comparing multiple logistic regression models predicting each psychopathological outcome from specific covariates and NuPDQ, PREPS, and NuPCI scores. Results: 42.8% of the sample reported significant levels of anxiety, while 10.3% were positive on depression screening and 13.1% on OCD screening. No significant difference was found in the prevalence of high anxiety, depression, or OCD screening scores compared with the first pandemic wave. Controlling for covariates, we found that GAD-7 and PHQ-2 scores were predicted by pregnancy-specific stress; positive OCD screening was not. The model of high anxiety was improved by adding pandemic-related stress as a predictor (in particular, feeling unprepared for delivery and postpartum). Finally, coping strategies (avoidance, spiritual coping, and planning-preparation) significantly improved prediction of all three psychopathological outcomes. Conclusions: The present study suggests the importance of pregnancy-related stress, COVID-19 pandemic stress, and of coping strategies in counteracting or contributing to psychiatric symptomatology during the current pandemic.